LGBT Novel Drug Use as Contextualized Through Control, Strain, and Learning Theories*. (26th September 2016) - Rukus, Joseph; Stogner, John; Miller, Bryan
Abstract : Objective: We examine novel drug use in the lesbian, gay, bisexual, and transgender (LGBT) community in the context of social learning, self‐control, and strain theories. Methods: Based on a sample of 2, 349 college students, we examine novel drug use rates of LGBT participants. We then perform a series of logistic regression models to examine factors correlated with LGBT novel drug use. Results: We find LGBT individuals have higher rates of use for novel drugs. We find that social learning constructs partially mediate the relationship between sexual orientation and novel drug use. The data did not support the hypotheses that strain or self‐control mediated or acted as a moderator in this relationship. Conclusion: We hypothesize higher LGBT novel drug use may be related to unique cultural definitions surrounding LGBT drug use and LGBT individuals being less likely to stigmatize substance use. This finding may have implications for LGBT substance use messaging and education programs.